Differences in the semen quality of Apis mellifera drones of selected lines along reproductive season in Balcarce district, Southeastern Buenos Aires Province, Argentina - Meroi Arcerito, Facundo René (2023)
Sperm quality in Apis mellifera drones plays a central role in colony reproduction. Several authors claimed that semen quality varies according to intrinsic and extrinsic factors. However, paramount and basic issues are unresolved in disentangling the factors affecting sperm quality. Here we explored if different dates within the reproductive season exhibit variation in sperm quality of drones from colonies selected under a template climate. Drones come from colonies of the Honeybee genetic program (MEGA-INTA), where lineages of brood disease tolerances are reared along with other features sought by the apiculture sector. The essay consists of three sampling times (T1, T2, T3) involving the whole reproductive season (from November to February), where T1 represents the beginning, T2 the middle, and T3 the ending reproductive season. Eight hives were assessed twice per sampling time. The techniques used were Eosina-Nigrosina for viability, Osmotic Swelling test (HOST) to test cell membrane function by using distilled water 100 OSM at 22°C and 35°C, concentration (number of spermatic cells estimation per volume of semen) through a Newbauer chamber, the number of drones matures with semen (total drones evaluated/drones with ejection of semen under abdomen stimulation), and the obtained sperm volume per drone (obtained volume/number of drone with semen) per colony. Results suggest T2 has better viability than T1 and T3 (Mann-Whitney: p= 0,00189 and p=0,005264, respectively). In HOST with distilled water, T2 differs from T3 (Mann-Whitney: p=0,01344). At 100 OSM at 22°C, there were no differences (all P＞0.05), and at 100 OSM at 35°C, we only registered differences between T2 and T3 (Mann-Whitney: p=0,01639). In Concentration, T2 had more sperm cells than T1 and T3 (Mann-Whitney: p=1,05E-05 and p= 2,25E-06, respectively). In semen volume per drone and the number of mature drones with semen, there were no differences (all P＞0.05). Our results suggest variation in semen quality through the reproductive season. Hence, in the sampling region, we recommend using reproductive techniques involving semen manipulation, preferably in January (T2), involving better quality semen.